THE MEANING OF AGRICULTURE AND TOURISM ACTIVITIES FOR TENGGER SOCIETY IN WONOKITRI VILLAGE, TOSARI DISTRICT, PASURUAN OF REGENCY - Utomo, Medea Ramadhani; Hidayat, Kliwon; Yuliati, Yayuk (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2015)
Tengger people's life could not be discharged to nature. Human ecology, a science that describes the interaction of humans and the environment, led to a meaning through the approach of symbolic interactionism and encourage human behavior towards nature. The phenomenon has become the foundation of this research problems. The first objective is reviewing the meaning of farming and tourism services and the relationship between them. The second, linking these two aspects to the behavior of the local community conservation. Third, emphasizing religious activity and its relationship to farming, tourism services, and the local community conservation. In the economic sphere, the relationship activities of farming and tourism services lasted in a synergistic, integrated and encourage one another. As the positive impact, ecotourism was a solution encouraging the Tengger community to give a positive response on the application of conservation agriculture on the dry land, as the efforts to prevent and repair environmental damage. In the culture and religious teachings of Tengger community, there were some important parts of the community, such as certain spells, and the law of Karmapala and the mlaspals ceremony (temple purification) to the safety of humans and nature, at onfarm and tourism activities of live.